Pregnant women's use and attitude toward herbal, vitamin, and mineral supplements in an academic tertiary care center, Riyadh, Saudi Arabia - Mohammed Al Essa; Abdulrahman Alissa; Abdalrhman Alanizi; Rami Bustami; Feras Almogbel; Omar Alzuwayed; Meshari Abo Moti; Nouf Alsadoun; Wasmiyah Alshammari; Abdulkareem Albekairy; Shmeylan Al Harbi; Mohammed Alhokail; et al. (Elsevier, 2019)
Background: Herbal medicine has been widely utilized by pregnant women despite the limited available evidence regarding the safety and efficacy of that practice. The current available studies, from different countries, estimated that the use of herbal medicine during pregnancy range from 7% up to 96%. The aim of this study is to determine the prevalence, attitude, source of information, and reasoning behind the use of herbal medicine among pregnant women in Saudia Arabia. Methods: A cross-sectional study conducted using a convenience sample including pregnant women who visited the obstetric clinics at King Abdulaziz Medical City in Riyadh, Saudi Arabia. A survey was administered in order to evaluate the prevalence and perception toward herbal medicine use among pregnant women in Saudi Arabia. Results: A total of 297 pregnant women completed the survey. The results showed that 56% of the respondents have used some type of herbal medicine during their pregnancy. Olive oil was utilized in 26% of the respondents followed by cumin 20% and garlic 15%. In addition, 37% of the respondents used herbal medicine by their own initiative, while 33% and 12% used herbal medicine based on recommendations from their families and friends, respectively. Furthermore, 19% of the respondents reported a positive attitude toward herbal medicine use during pregnancy. In addition, the percentage of women with positive attitude was marginally higher among respondents with lower educational level. Conclusion: The prevalence of using herbal medicine is considerably high among pregnant women in Saudi Arabia. Unfortunately, the majority of the users relied on informal sources to use herbal medicine during pregnancy. Keywords: Herbal medicine, Supplements, Pregnancy, Prevalence, Attitudes, Saudi Arabia